Prevention of Alveolar Bone Loss in an Osteoporotic Animal Model via Interference of Semaphorin 4d. (November 2014) - Zhang, Y.; Wei, L.; Miron, R.J.; Zhang, Q.; Bian, Z.
Semaphorin 4d (Sema4d) has been proposed as a novel target gene for the treatment of osteoporosis. Recently, we fabricated a site-specific bone-targeting system from polymeric nanoparticles that demonstrates an ability to prevent bone loss in an osteoporotic model by interfering with Sema4d gene expression using small interference RNA (siRNA) molecules. The aim of the present investigation was to determine the effects of this targeting system on the periodontium, an area of high bone turnover. We demonstrated, by single photon emission computed tomography, that intravenous injection of this molecule in ovariectomized Balb/C mice is able to target alveolar bone peaking 4 hr post-injection. We then compared, by histological analysis, the bone volume/total volume (BV/TV), alveolar bone height loss, immunohistochemical expression of Sema4d, and total number of osteoclasts in mandibular alveolar bone. Four treatment modalities were compared as follows: (1) sham-operated, (2) OVX-operated, (3) OVX+estrogen replacement therapy, and (4) OVX+siRNA-Sema4d animals. The results from the present study demonstrate that an osteoporotic condition significantly increases alveolar bone height loss, and that the therapeutic effects via bone-targeting systems featuring interference of Sema4d are able to partly counteract alveolar bone loss caused by osteoporosis. While the future therapeutic demand for the large number of patients suffering from osteoporosis faces many challenges, we demonstrate within the present study an effective drug-delivery moiety with anabolic effects on the bone remodeling cycle able to locate and target alveolar bone regeneration.